2016
DOI: 10.1002/ejlt.201600184
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lipid composition on the oral bioavailability of cinnarizine sub‐microemulsions

Abstract: The oral bioavailability of cinnarizine is usually limited by its poor solubility in the gastrointestinal tract. In this study, two kinds of cinnarizine sub‐microemulsions (SMEs) were prepared using medium (MCT) and long (LCT) chain triglycerides, respectively, and the effect of the lipid composition on the oral bioavailability of SMEs was investigated in terms of stability, in vitro lipolysis, in situ single‐pass intestinal perfusion, and in vivo pharmacokinetics. The SMEs increased cinnarizine stability in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The high calcium permeability of CBP-Ca indicated that, in combination with CBP, the calcium transported rapidly into enterocytes [ 33 , 36 ]. Thus, the calcium in the peptide-bound state is superior to the free calcium ions in term of intestinal calcium absorption.…”
Section: Resultsmentioning
confidence: 99%
“…The high calcium permeability of CBP-Ca indicated that, in combination with CBP, the calcium transported rapidly into enterocytes [ 33 , 36 ]. Thus, the calcium in the peptide-bound state is superior to the free calcium ions in term of intestinal calcium absorption.…”
Section: Resultsmentioning
confidence: 99%